(untitled) (Tempo e Argumento, 2021)
The historical narrative of Mozambican as an independent State had, as its main sources, the direct witnesses who carried out the struggle for liberation and thus exerted important roles in the new independent State, starting from 1975. It was this narrative which formed a historiography which became official, contested by different orientations, developed as inside, as outside Mozambique. The research here presented aims at providing the point of view of one of these tendencies, that of the site online macuablogs, whose title is “Mozambique for all” (https://macua.blogs.com/moambique_para_todos/), which expresses a counter-narration of a national history, embedded in a political vision contrary to Frelimo and its government. This attempt is made starting from a political position contrary to the current government led by Frelimo. This research selected all the historical articles published in the site, analyzing its main issues, complementing such work with an interview to the founder and manager of the blog, the Portuguese Fernando Gil. As a result, the evidences discovered opened a new room for a public and broad debate to rethink Mozambican history, providing an interesting documentation for the work of the professional historian. Keywords: official historiography; historiographical review; mozambican struggle for liberation; human rights violation.